2005
DOI: 10.1097/01.tp.0000158355.83327.62
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-Reperfusion Injury Activates Innate Immunity in Rat Kidneys

Abstract: I/R injury rapidly activates the innate immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
144
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(160 citation statements)
references
References 28 publications
11
144
1
4
Order By: Relevance
“…In the present study, the TLR4 mRNA expression levels in the kidneys were markedly increased in the HS5 and HS10 groups compared with the control group, demonstrating that the kidneys were seriously impacted by AHS. In addition, previous research has shown a marked increase in TLR2 and TLR4 expression in renal tubular cells and in renal infiltrating cells caused by ischemia and reperfusion injury compared with control group (Kim et al, 2005;Pedregosa et al, 2011). Cunningham et al (2004) reported that TLR4 expression in the kidneys was critical in mediating LPS-induced acute kidney failure via proinflammatory cytokine release and subsequent kidney damage.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the TLR4 mRNA expression levels in the kidneys were markedly increased in the HS5 and HS10 groups compared with the control group, demonstrating that the kidneys were seriously impacted by AHS. In addition, previous research has shown a marked increase in TLR2 and TLR4 expression in renal tubular cells and in renal infiltrating cells caused by ischemia and reperfusion injury compared with control group (Kim et al, 2005;Pedregosa et al, 2011). Cunningham et al (2004) reported that TLR4 expression in the kidneys was critical in mediating LPS-induced acute kidney failure via proinflammatory cytokine release and subsequent kidney damage.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4-deficient mice have reduced myocardial infarction size 24 h after 1-h ligation of the left anterior descending coronary artery (35) and reduced levels of aspartate aminotransferase 1 and 3 h after reperfusion of liver lobes rendered ischemic for 45 min (53). TLRs were implicated in a rat model of renal IRI, but the earliest studies were performed 24 h after reperfusion (25). TLR4 protein and mRNA were elevated for days after renal IRI, and TLR4Ϫ/Ϫ as well as MyD88Ϫ/Ϫ animals had less renal dysfunction and less histological evidence of IRI 24 h after reperfusion (52).…”
Section: Discussionmentioning
confidence: 99%
“…These PRR include the toll-like receptor (TLR) family of innate immune receptors (4). In organ transplantation, DAMPs formed as a result of ischemia/reperfusion injury activate the innate immune system (86,94,135). Thus, infection and transplantation generate an inflammatory response by activating the MPS, resulting in the production of cytokines and chemokines and priming of the adaptive immune system (42).…”
Section: The Mononuclear Phagocyte Systemmentioning
confidence: 99%